Deep eutectic solvents coupled with (NH4)3H6CoMo6O24 trigger aerobic oxidation of 5-hydroxymethylfurfural to 5-formyl-2-furancarboxylic acid. Issue 58 (30th June 2022) - Sun, Yanbin; Yang, Kaixuan; Zhu, Zhiguo; Su, Ting; Ren, Wanzhong; Lü, Hongying
Abstract : A method for selective aerobic oxidation of HMF to FFCA over an Anderson-type POM (NH4 )3 H6 CoMo6 O24 catalyst in DESs was developed, which exhibited outstanding catalytic performance. Abstract : An Anderson-type polyoxometalate (NH4 )3 H6 CoMo6 O24 in deep eutectic solvents exhibited outstanding catalytic performance for the selective aerobic oxidation of HMF to FFCA. It is potentially a promising and highly environmentally friendly approach for biomass conversion.